Non-stationary response analysis of a high-rise building in Haikou during typhoons - Hu, Jiaxing; Li, Zhengnong; Zhao, Zhefei (Journal of Civil Engineering and Management, 2023)
From 2014 to 2016, several wind resistant field measurements were conducted to the high-rise building in Haikou. Based on these measurements, the present paper disclosed the characteristics of the time-history responses of axial acceleration on different floors during four typhoons, including the Rammasun, Kalmaegi, Mujigae and Sarika typhoons. The modal parameters of the measured building were identified by Morlet time-frequency wavelet transform methods, and the amplitude-dependent modal damping ratios and frequencies along translational directions were investigated. The results show that the variation trend of modal frequency with acceleration amplitude identified by the Morlet wavelet is the same as that recognized by time-domain method, while it is scattered with the interval bar (min-average-max) due to the nonstationary response of typhoon. Meanwhile, the larger the amplitude of acceleration response of high-rise buildings under strong wind, the greater the time-varying fluctuation of modal parameters identified by wavelet transform, and the bigger the difference between the interval bar (min-average-max). The full-scale study is expected to provide useful information on the wind-resistant design of high-rise buildings in typhoon-prone regions.